Melt pool dynamics and pore formation in selective laser melting: Mechanisms and microstructural insights - Jiafei Pang; Liming Huang; Hailin Liu; Xin Yi (Materials & Design)
Selective laser melting (SLM) is an advanced additive manufacturing technique, yet its application for structural components is often constrained by porosity-related defects. This study elucidates keyhole collapse and pore formation mechanisms through single-track simulations, combining ray-tracing-based heat source modeling and computational fluid dynamics (CFD) to analyze melt pool dynamics. Depending on the ratio of laser power density to scanning speed, two distinct melt pool behaviors are analyzed: keyhole mode and conduction mode. In the keyhole mode, protrusions on the front and rear keyhole walls, driven by recoil pressure and reflected laser rays, merge to trap gas, causing truncation and pore formation. Alternatively, backfilling, driven by surface tension during excessive keyhole curvature, allows gas escape and avoids pore defect formation. In the conduction mode, smaller protrusions and stable melt pool behavior without collapse are observed, with melt pool depth fluctuations attributed to nonuniform powder distribution. Coupling CFD with a cellular automaton model highlights the dual impact of pores on material microstructure: grain growth obstruction leads to coarser grains above pores, while reduced thermal gradients near pores promote fine grain formation. These findings deepen understanding of pore formation and its microstructural effects, providing insights to optimize SLM processes for enhanced material performance.